Experience with Coeliac Axis Compression Syndrome - Edwards, A. J. (1970)
Seven patients with “coeliac axis compression syndrome” are reported. Five were treated surgically, but only two did well. A survey of 200 healthy adults showed epigastric bruits in 6·5%; only one of these had dyspepsia, though dyspepsia was present in 12·5% overall. Caution is urged in attributing a causal relationship between coeliac axis compression and pain and in proceeding to arteriography when compression is suspected on clinical grounds.